P137 Establishment of a cohort to identify factors influencing return to work in the over 50s participating in the uk work programme: supporting older people into employment (SOPIE). (1st September 2016) - Brown, Judith; McQuaid, Ronald; Katikireddi, Srinivasa Vittal; Leyland, Alastair; Frank, John; Jeavons, Luke; Pellette, Paul de; Macdonald, Ewan
Abstract : Objectives: Supporting people back into employment after a period on welfare benefits is an important policy goal in many countries but difficult to achieve for people aged over 50 and those out of work for health reasons. The study's objective was to establish a cohort of clients engaging with the UK Government's return to work (RTW) initiative, the Work Programme (WP), to investigate the relationship between health, worklessness and the RTW process. Methods: A partnership between Ingeus (a WP provider), the data controller (the Department for Work and Pensions) and the academic team was established which allowed the development of a cohort of WP clients who would be followed up for the two years they were engaged in the WP and beyond. Using routine operational data (matched with area characteristics, employment outcomes (including progress towards work) and variations by client characteristics, including health), effects of interventions received and external factors were investigated. Results: The cohort contains 14, 258 clients aged 16 to 64 (20.2% over 50) who entered the WP in Scotland between April 2013 and July 2014. At baseline 43.4% of clients self-reported health concerns affecting their ability to work. Preliminary analysis indicates that, of the clients who have completed the full 2 years on the WP, 44.9% had a job start and 55.1% remained out of work. 73% of clients with a job start had accumulated 3+ months in work. Analysis is taking place to fully characterise the factors influencing RTW. Conclusions: The establishment of this cohort provides a unique opportunity to investigate the relationship between health, worklessness and the RTW process in a hard-to-reach population. The results will provide new information on the interventions, support and individual factors which assist the over 50s return to and sustain in work.